Tsunamis from strike-slip earthquakes in the Wharton Basin, northeast Indian Ocean: March 2016 Mw7.8 event and its relationship with the April 2012 Mw 8.6 event. Issue 3 (20th September 2017) - Heidarzadeh, Mohammad; Harada, Tomoya; Satake, Kenji; Ishibe, Takeo; Takagawa, Tomohiro
Summary: The Wharton Basin, off southwest Sumatra, ruptured to a large intraplate left-lateral strike-slip M w 7.8 earthquake on 2016 March 2. The epicentre was located ∼800 km to the south of another similar-mechanism intraplate M w 8.6 earthquake in the same basin on 2012 April 11. Small tsunamis from these strike-slip earthquakes were registered with maximum amplitudes of 0.5−1.5 cm on DARTs and 1−19 cm on tide gauges for the 2016 event, and the respective values of 0.5−6 and 6−40 cm for the 2012 event. By using both teleseismic body waves and tsunami observations of the 2016 event, we obtained optimum slip models with rupture velocity ( Vr ) in the range of 2.8–3.6 km s −1 belonging to both EW and NS faults. While the EW fault plane cannot be fully ruled out, we chose the best model as the NS fault plane with a Vr of 3.6 km s −1, a maximum slip of 7.7 m and source duration of 33 s. The tsunami energy period bands were 4−15 and 7−24 min for the 2016 and 2012 tsunamis, respectively, reflecting the difference in source sizes. Seismicity in the Wharton Basin is dominated by large strike-slip events including the 2012 ( M w 8.6 and 8.2) and 2016 ( M w 7.8) events, indicating that these events are possible tsunami sources in the Wharton Basin. Cumulative number and cumulative seismic-moment curves revealed that most earthquakes are of strike-slip mechanisms and the largest seismic-moment is provided by the strike-slip earthquakes in this basin.